Registered nurse maternal newborn nursing care review module - Treas, Leslie Schaaf; Wilkinson, Judith M. (Assessment Technologies, 2005)
This review module is a component of the Comprehensive Assessment and Review Program and is designed to be used in conjunction with content area exams. It includes key points and critical thinking exercises (with answer keys) for nursing management for a variety of conditions